Effects of meteorological variability on chemical changes in two hydrologically distinct prairie-pothole wetlands - Kui Hu; David M. Mushet; Jon N. Sweetman (Journal of Hydrology, 2025)

Multiproxy paleolimnological records provide evidence for a shift to a new ecosystem state in the Northern Great Plains, USA - Kui Hu; David M. Mushet; Jon N. Sweetman (Limnology and Oceanography, 2023)
Wetlands in the Prairie Pothole Region of the North American Northern Great Plains perform multiple ecosystem services and are biodiversity hotspots. However, climatological changes can result in sudden shifts in these important ecosystems. For example, marked increases in precipitation in the last few decades have resulted in a widespread shift in wetlands across the Prairie Pothole Region to a new ecohydrological state. We used multiproxy analyses (diatom community composition and invertebrate stable isotopes) of 210 Pb‐dated sediment cores from two adjacent, but morphologically and hydrologically different, prairie‐pothole wetlands to assess the effects of hydroclimatic variability on these wetland ecosystems. Our results provide evidence that the recent ecohydrological shift in the region's wetlands is unprecedented over the past ca. 178 yr. Oxygen stable isotopes in chironomid head capsules provide a record of paleohydrology changes. The most recent sediments (i.e., those deposited after the state shift) from both wetlands revealed novel changes in diatom communities that differed greatly from earlier community compositions. In addition, a depleted signal in deuterium and 13 C carbon stable isotopes observed in chironomid head capsules and Daphnia ephippia, respectively, after 1993 is likely related to an increase in methane production in these wetlands. Our study highlights the importance of considering basin morphometry including whether a wetland has an overflow point, and multiple biological indicators to study climate‐change influences on freshwater ecosystems. Research using these techniques can lead to an improved understanding of recent ecosystem shifts, an understanding that will be essential for future climate‐change adaptation and mitigation in this ecologically important region.

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Chemical Connectivity and Multi-Element Composition of Groundwater in Depressional Wetlands - Yuxiang Yuan; Xiaoyan Zhu; David M. Mushet; Matthew J. Solensky; Marinus L. Otte (Wetlands, 2021)

Upland burning and grazing as strategies to offset climate-change effects on wetlands - Owen P. McKenna; David A. Renton; David M. Mushet; Edward S. DeKeyser (Wetlands Ecology and Management, 2021)
Wetland ecosystems perform a multitude of services valued by society and provide critical habitat for migratory birds and other wildlife. Despite their importance, wetlands have been lost to different local, regional, and global drivers. Remaining wetlands are extremely sensitive to changing temperature and precipitation regimes. Management of grassland areas in wetland catchments may be an effective strategy for counteracting potentially negative impacts of climate change on wetlands. Our objective was to estimate the effects of climate changes on wetland hydrology, and to explore strategies for increasing surface-water inputs to wetlands. We coupled a field study with process-based simulation modeling of wetland-water levels. We found that climate change could decrease the number of wetlands that hold ponded water during the waterfowl breeding season by 14% under a hot wet scenario or 29% under a hot dry scenario if no upland-management actions were taken. Upland burning reduced pond losses to 9% (hot wet) and 26% (hot dry). Upland grazing resulted in the smallest loss of ponded wetlands, 6% loss under the hot-and-wet scenario and 22% loss under the hot-and-dry scenario. Overall, water inputs could be increased by either burning or grazing of upland vegetation thereby reducing pond losses during the waterfowl breeding season. While field results suggest that both grazing and burning can reduce the vegetative structure that could lead to increases in runoff in grassland catchments, our model simulations indicated that additional actions may be needed for managers to minimize future meteorologically driven water losses.

Climate‐ versus geographic‐dependent patterns in the spatial distribution of macroinvertebrate assemblages in New World depressional wetlands - Cristina Stenert; Mateus M. Pires; Luis B. Epele; Marta G. Grech; Leonardo Maltchik; Kyle I. McLean; David M. Mushet; Darold P. Batzer (Global Change Biology, 2020)
Analyses of biota at lower latitudes may presage impacts of climate change on biota at higher latitudes. Macroinvertebrate assemblages in depressional wetlands may be especially sensitive to climate change because weather‐related precipitation and evapotranspiration are dominant ecological controls on habitats, and organisms of depressional wetlands are temperature‐sensitive ectotherms. We aimed to better understand how wetland macroinvertebrate assemblages were structured according to geography and climate. To do so, we contrasted aquatic‐macroinvertebrate assemblage structure (family level) between subtropical and temperate depressional wetlands of North and South America using presence–absence data from 264 of these habitats across the continents and more‐detailed relative‐abundance data from 56 depressional wetlands from four case‐study locations (North Dakota and Georgia in North America; southern Brazil and Argentinian Patagonia in South America). Both data sets roughly partitioned wetland numbers equally between the two climatic zones and between the continents. We used ordination methods (PCA and NMDS) and tests of multivariate dispersion (PERMDISP) to assess the distribution and the homogeneity in variation in the composition of macroinvertebrate assemblages across climates and continents, respectively. We found that macroinvertebrate assemblage structures in the subtropical depressional wetlands of North and South America were similar to each other (at the family level), while assemblages in the North and South American temperate wetlands were unique from the subtropics, and from each other. Tests of homogeneity of multivariate dispersion indicated that family‐level assemblage structures were more homogeneous in wetlands from the subtropical than the temperate zones. Our study suggests that ongoing climate change may result in the homogenization of macroinvertebrate assemblage structures in temperate zones of North and South America, with those assemblages becoming enveloped by assemblages from the subtropics. Biotic homogenization, more typically associated with other kinds of anthropogenic factors, may also be affected by climate change.

Modeling the Supporting Ecosystem Services of Depressional Wetlands in Agricultural Landscapes - David M. Mushet; Cali L. Roth (Wetlands, 2020)
We explored how a geographic information system modeling approach could be used to quantify supporting ecosystem services related to the type, abundance, and distribution of landscape components. Specifically, we use the Integrated Valuation of Ecosystem Services and Tradeoffs model to quantify habitats that support amphibians and birds, floral resources that support pollinators, native-plant communities that support regional biodiversity, and above- and below-ground carbon stores in the Des Moines Lobe ecoregion of the U.S. We quantified services under two scenarios, one that represented the 2012 Des Moines Lobe landscape, and one that simulated the conversion to crop production of wetlands and surrounding uplands conserved under the USDA Agricultural Conservation Easement Program (ACEP). While ACEP easements only covered 0.35% of the ecoregion, preserved wetlands and grasslands provided for 19,020 ha of amphibian habitat, 21,462 ha of grassland-bird habitat, 18,798 ha of high-quality native wetland plants, and 27,882 ha of floral resources for pollinators. Additionally, ACEP protected lands stored 257,722 t of carbon that, if released, would result in costs in excess of 45-million USD. An integrated approach using results from a GIS-based model in combination with process-based model quantifications will facilitate more informed decisions related to ecosystem service tradeoffs.

Invertebrate communities of Prairie-Pothole wetlands in the age of the aquatic Homogenocene - Kyle I. McLean; David M. Mushet; Jon N. Sweetman; Michael J. Anteau; Mark T. Wiltermuth (Hydrobiologia, 2020)

Can Multi-Element Fingerprinting of Soils Inform Assessments of Chemical Connectivity Between Depressional Wetlands? - Xiaoyan Zhu; Yuxiang Yuan; David M. Mushet; Marinus L. Otte (Wetlands, 2019)

Temporal gamma-diversity meets spatial alpha-diversity in dynamically varying ecosystems - David M. Mushet; Matthew J. Solensky; Shay F. Erickson (Biodiversity and Conservation, 2019)

Accommodating State Shifts within the Conceptual Framework of the Wetland Continuum - David M. Mushet; Owen P. McKenna; James W. LaBaugh; Ned H. Euliss; Donald O. Rosenberry (Wetlands, 2018)

Evidence for a climate-induced ecohydrological state shift in wetland ecosystems of the southern Prairie Pothole Region - Owen P. McKenna; David M. Mushet; Donald O. Rosenberry; James W. LaBaugh (Climatic Change, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Controls on the Geochemical Evolution of Prairie Pothole Region Lakes and Wetlands Over Decadal Time Scales - Martin B. Goldhaber; Christopher T. Mills; David M. Mushet; Blaine B. McCleskey; Jennifer Rover (Wetlands, 2016)

Interannual Water-level Fluctuations and the Vegetation of Prairie Potholes: Potential Impacts of Climate Change - Arnold van der Valk; David M. Mushet (Wetlands, 2016)

Aquatic-Macroinvertebrate Communities of Prairie-Pothole Wetlands and Lakes Under a Changed Climate - Kyle I. McLean; David M. Mushet; David A. Renton; Craig A. Stockwell (Wetlands, 2016)

Midcontinent Prairie-Pothole Wetlands and Climate Change: an Introduction to the Supplemental Issue - David M. Mushet (Wetlands, 2016)

Intermittent Surface Water Connectivity: Fill and Spill Vs. Fill and Merge Dynamics - Scott G. Leibowitz; David M. Mushet; Wesley E. Newton (Wetlands, 2016)

Changes in Pond Water Levels and Surface Extent Due to Climate Variability Alter Solute Sources to Closed-Basin Prairie-Pothole Wetland Ponds, 1979 to 2012 - James W. LaBaugh; David M. Mushet; Donald O. Rosenberry; Ned H. Euliss; Martin B. Goldhaber; Christopher T. Mills; Richard D. Nelson (Wetlands, 2016)

From “Duck Factory” to “Fish Factory”: Climate Induced Changes in Vertebrate Communities of Prairie Pothole Wetlands and Small Lakes - Kyle I. McLean; David M. Mushet; Craig A. Stockwell (Wetlands, 2016)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

Potential for parasite-induced biases in aquatic invertebrate population studies - Justin D. L. Fisher; David M. Mushet; Craig A. Stockwell (Hydrobiologia, 2014)

Influence of Conservation Programs on Amphibians using Seasonal Wetlands in the Prairie Pothole Region - Caleb J. Balas; Ned H. Euliss; David M. Mushet (Wetlands, 2012)

A Multi-Year Comparison of IPCI Scores for Prairie Pothole Wetlands: Implications of Temporal and Spatial Variation - Ned H. Euliss; David M. Mushet (Wetlands, 2011)

Classifying the Hydrologic Function of Prairie Potholes with Remote Sensing and GIS - Jennifer Rover; Chris K. Wright; Ned H. Euliss; David M. Mushet; Bruce K. Wylie (Wetlands, 2011)

The wetland continuum: A conceptual framework for interpreting biological studies - Ned H. Euliss; James W. LaBaugh; Leigh H. Fredrickson; David M. Mushet; Murray K. Laubhan; George A. Swanson; Thomas C. Winter; Donald O. Rosenberry; Richard D. Nelson (Wetlands, 2004)

Using aquatic invertebrates to delineate seasonal and temporary wetlands in the prairie pothole region of North America - Ned H. Euliss; David M. Mushet; Douglas H. Johnson (Wetlands, 2002)

Floristic quality assessment of one natural and three restored wetland complexes in North Dakota, USA - David M. Mushet; Ned H. Euliss; Terry L. Shaffer (Wetlands, 2002)

Use of macroinvertebrates to identify cultivated wetlands in the Prairie Pothole Region - Ned H. Euliss; David M. Mushet; Douglas H. Johnson (Wetlands, 2001)

Influence of agriculture on aquatic invertebrate communities of temporary wetlands in the Prairie Pothole Region of North Dakota, USA - Ned H. Euliss; David M. Mushet (Wetlands, 1999)